“He Sees Me as His Possession and Thinks He Can Do What He Wants.” Dependent Stay and Partner Violence among Moroccan Marriage Migrant Women in the Netherlands - Bartels, Edien (Journal of Muslim minority affairs, 2021)
Partner violence, including physical, psychological, and sexual violence, is a problem in the Netherlands, just as it is all over the world. A special category of women who are affected by these forms of violence are marriage migrants; a group that is particularly vulnerable in the first five years after migration to the Netherlands because of their dependence on their partner for residence rights. This article, based on qualitative research among Moroccan women in the Netherlands, examines the position of this group of women and analyses the role that dependent residence plays in partner violence. In the Netherlands, a process of “culturalization of male-female relationships” is going on, for migrant couples, especially for Muslims. Male-female relations and violence against women are explained by reference to Islam or cultural concepts such as “group culture”, “honour and shame”. In this article we argue how legal regulations in the surrounding society play an important role.